RESPON PERTUMBUHAN MISELIA G3 FP005 FAPERTA UNSIKA PADA MEDIA BIAKAN MURNI YANG BERBEDA - Astri Dwi Widianingsih; Bastaman Syah; Vera Oktavia Subardja; Ani Lestari (Jurnal Agrotech, 2024)
The Indonesian region has quite high air humidity and is ideal for the growth of straw mushrooms. To obtain pure cultures of straw mushrooms, you can go through the pure culture or G0 culture stage, then from G0 sub-cultures are carried out into G1, G2, G3 and G4. This research aims to obtain the best pure culture media for the growth of G3 FP005 Faperta Unsika mycelia. The research was carried out at the Biotechnology and Plant Breeding Laboratory, Faculty of Agriculture, Singaperbangsa University, Karawang, from April to May 2023. The research method used was a single factor Completely Randomized Design (CRD) with 7 treatments and 5 replications: PDA 100% (A), Charcoal Husk 100 % (B), 100% Husk (C), 75% PDA + 25% Husk Charcoal (D), 80% PDA + 20% Husk Charcoal (E), 50% Husk Charcoal + 50% Husk Charcoal (F), and PDA 50% + Charcoal Husk 25% + Husk 25% (G). Treatments were analyzed using variance and F test at 5% level, to find out the best treatment followed by further DMRT (Duncan Multiple Range Test) at 5% level. The results of the research were that there was a real effect of using several pure cultures on the growth of G3 FP005 mycelia. PDA 75% + Charcoal Husk 25% media gave the highest diameter at 2 dai (2.24 cm), 3 dai (4.78) and 4 dai (7.19 cm), the highest growth rate was (2.52 cm), diameter regression with R2 0.898 then P value 0.052047, and growth rate regression with R2 0.68 then P value 0.410604.